PENGEMBANGAN MEDIA PEMBELAJARAN DENGAN APLIKASI WORKED EXAMPLE BERBANTUAN ANDROID UNTUK MENINGKATAKAN PRESTASI BELAJAR (Studi Pada Mata Pelajaran Fisika Kelas X Di SMA Negeri 1 Pagar Alam) - Laily Ramadhani; Bambang Sahono (UNIB Press, 2021)
The aims of this research is to describe the learning media with the android assisted worked example application which is feasible to improve learning achievement and Describing the effectiveness of learning media with the android assisted worked example application in improving learning achievement. In this research, the development design (Research and Development) was used. The research subjects were students of class X MIPA at SMA Negeri 1 Pagar Alam. The data collection techniques used in the research were assessment sheets and student test results. This research data analysis with mean and t-test. The validation instrument for media and material experts in the research was a Likert scale. The conclusion of this research is the learning media with the android assisted worked example application developed are feasible to improve learning achievement and the development of learning media with the android assisted worked example application effective in improving learning achievement based on the results of limited trials and broad scale tests for class X MIPA SMA Negeri 1 Pagar Alam on Work and Energy Physics subject matter